ANALISA PEMIKIRAN TOKOH MUSLIM KONTEMPORER ALI ABDUL HALIM MAHMUD - Meilani, Muna; Arif, Mahmud (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
Abstract: Dr. Ali Abdul Halim Mahmoud is one of the contemporary Muslim intellectuals who believes that there are noble tools in his book. Noble tools, The main source of human moral education is the Qur'an and the Sunnah. An Nur: 47-53 The concept of Islamic education in the letter of Ali Abdul Halim Mahmud aims to emphasize various aspects of Aqeedah (Tawhid), Shari'ah and Islamic Morality. The aspects of education contained in Surat An Nur: 47-53 are: the educator is Allah Subhanallahu Ta'ala and the Messenger of Allah Shollahu alaihi wassalam, and the learners are believers, hypocrites and Jews. Moral education, the way of education includes information, conditions, commands, and suggestions for understanding the form. Ali Abdul Halim Mahmud was a modern Sufi figure, even known as Al Ghozali in the 14th century. He suggested how to coordinate and integrate general education and Islamic religious education towards Allah Subhanallahu Ta'ala (Allah Subhanallahu Ta'ala). Keywords: Ali Abdul Halim Mahmoud, Contemporary Islamic Education